PO.4.79 Nailfold capillary changes in patients with systemic lupus erythematous. (27th September 2022) - Stefania, S; Rotondo, C; Sciacca, S; Cantatore, FP; Corrado, A
Abstract : Purpose: This study aims to investigate nailfold capillary (NF) changes in patients with Systemic Lupus Erythematous (SLE), and its association with disease activities, autoantibodies, clinical symptoms. Methods: 52 patients were enrolled (7 m and 45 f), between 2015 and 2022, and underwent to NF. Alterations in capillary morphology, diameter, architecture and density were analyzed. CSURI index was calculated. Clinical symptoms and autoantibodies were reported. Disease activity was evaluated by SLE disease index (SLEDAI). Results: 46% of the enrolled patients showed non-specific pattern, 6% early scleroderma pattern (EAP), 18% like-scleroderma pattern (LSP), 26% normal pattern. The most frequent microvascular alterations were tortuous capillary (81%), edema (54%), enlarged capillaries (30%), capillary hemorrhage (26%), prominent subpapillary plexus (7%), giant capillaries (6%), elongated capillaries (6%) and bushy capillaries (6%). Considering disease activity, the patients in clinical remission highlighted in 60% of cases a normal NF pattern, in 40% non-specific pattern. The patients with moderate disease activity showed in 7% of cases EAP, and in 10% LSP. The patients with high disease activity evidenced in 6% of cases EAP, 41% LSP. The capillary abnormalities rates noticed in subgroups of patients relating disease activity, respectively low, moderate and high activity, were edema (20% vs 57% vs 65%), tortuous capillary (80% vs 80%, 94%), bushy capillaries (0% vs 4% vs 2%), elongated capillaries (0% vs 7% vs 6%), prominent subpapillary plexus (0% vs 2% vs 6%), capillary hemorrhage (40% vs 30% vs 18%), enlarged capillaries (0% vs 23% vs 53%; p=0, 031), giant capillaries (0% vs 7% vs 6%). Subdividing the LES patients on the basis of Raynaud's Phenomenon (RF) presence, those with RF, compared to patients without RF showed higher frequency of ESP (12, 5% vs 0%) and LSP (25% vs 14%). The most frequent capillary alterations evidenced in patients with RF compared with patients without RF were edema (58% vs 53%), tortuous capillary (95% vs 75%), enlarged capillaries (42% vs 21%), giant capillaries (12% vs 0%), disorganization of capillary array (4% vs 0%), bushy capillaries (8% vs 3%) and prominent subpapillary plexus (8% vs 7%). The patients without RF, compared to patients with RF presented more often a normal pattern (36% vs 17%) and non-specific pattern (56% vs 44%). The most frequent capillary abnormalities highlighted in patients without RF were elongated capillaries (7% vs 4%) and capillary hemorrhage (28% vs 25%). The patient with glomerulonephritis did not show significant differences compared to patients without glomerulonephritis. Conclusions several capillary alterations were founded in SLE patients. The association between disease activity and capillary changes was highlighted. In particular, moderate and high disease activities were often correlated to altered capillary pattern such as like and EAP, and to capillary abnormalities such as enlarged capillaries. Also, patients with RF showed a higher association with capillary alterations than patients without RF.